Association between primary graft dysfunction and acute kidney injury after orthotopic heart transplantation – a retrospective, observational cohort study. (9th May 2020) - Nicoara, Alina; Kretzer, Adam; Cooter, Mary; Bartz, Raquel; Lyvers, Jeffrey; Patel, Chetan B.; Schroder, Jacob N.; McCartney, Sharon L.; Podgoreanu, Mihai V.; Milano, Carmelo A.; Swaminathan, Madhav; Stafford‐Smith, Mark
Summary: Acute kidney injury (AKI) and primary graft dysfunction (PGD) are serious complications after heart transplantation (HT). The relationship between AKI and PGD is poorly understood. We sought to examine the incidence of AKI and identify risk factors associated with AKI. We hypothesized that PGD is one of the risk factors independently associated with post‐HT AKI. We gathered data for all adult patients who underwent HT between 2009 and 2014. AKI was defined by the KDIGO criteria. PGD was categorized using ISHLT criteria. We assessed univariable and multivariable logistic regression to identify risk factors independently associated with post‐HT AKI. Out of 316 patients, postoperative AKI occurred in 273 (86%) patients: 188 (68%) stage I, 44 (16%) stage II, and 41 (15%) stage III. Stage II/III AKI was associated with increased risk of mortality at 1 year. There was significant association between severe PGD and stage II/III AKI ( P  = 0.001, OR 3.63, 95% CI: 1.69–7.94). Other clinical factors significantly associated with stage II/III AKI included longer donor brain death duration and lower recipient baseline creatinine. We found that stage II/III AKI is common and independently associated with severe PGD. Another potentially modifiable risk factor is donor brain death duration.